Periodic orbits of a Hamiltonian system related with the Friedmann–Robertson–Walker system in rotating coordinates - Buzzi, Claudio [UNESP]; Llibre, Jaume; Santana, Paulo [UNESP] (Elsevier, 2020)
We provide sufficient conditions on the four parameters of a Hamiltonian system, related with the Friedmann–Robertson–Walker Hamiltonian system in a rotating reference frame, which guarantee the existence of 12 continuous families of periodic orbits, parameterized by the values of the Hamiltonian, which born at the equilibrium point localized at the origin of coordinates. The main tool for finding analytically these families of periodic orbits is the averaging theory for computing periodic orbits adapted to the Hamiltonian systems. The technique here used can be applied to arbitrary Hamiltonian systems.
Keywords: Averaging theory; Families of periodic orbits; Generalized Friedmann–Robertson–Walker Hamiltonian; Hamiltonian systems